2019
DOI: 10.7602/jmis.2019.22.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Totally Laparoscopic Distal Gastrectomy in Post Liver Transplant Patient

Abstract: The risk of malignancy after transplantation is higher than that of general population. Laparoscopic surgery has become a standard treatment of gastric cancer. However, there are no case reports evaluating totally laparoscopic gastrectomy in patients with previous liver transplantation. Herein we report our experience with a liver transplant recipient who underwent totally laparoscopic distal gastrectomy (TLDG) for gastric cancer. A 63 year-old man underwent orthotopic liver transplantation (OLT) for cryptogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Along with the recent preference for laparoscopic gastrectomy, it has been performed even in the LT recipients with gastric cancer. The world-first case of totally laparoscopic distal gastrectomy for gastric cancer was performed in a 63-year-old man who underwent LT for cryptogenic liver cirrhosis [16]. Eight years later, gastric cancer was diagnosed during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the recent preference for laparoscopic gastrectomy, it has been performed even in the LT recipients with gastric cancer. The world-first case of totally laparoscopic distal gastrectomy for gastric cancer was performed in a 63-year-old man who underwent LT for cryptogenic liver cirrhosis [16]. Eight years later, gastric cancer was diagnosed during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have demonstrated the safety and feasibility of laparoscopic surgery for primary gastric cancer [ 6 ]. However, reports on the laparoscopic approach for de novo gastric cancer after LT are limited [ 7 8 ]. Therefore, we aimed to evaluate the surgical safety and oncological outcomes of gastric cancer surgery including open and laparoscopic approaches.…”
Section: Introductionmentioning
confidence: 99%